COMMODIFICATION OF TOXIC RELATIONSHIP IN ALL TOO WELL, SHORT MOVIE ADAPTATION BY TAYLOR SWIFT - Aulia Meidiska; Dhita Hapsarini (Lingua Scientia, 2023)
The study aims to explore the transformation of the first (2012) and latest song All Too Well by Taylor Swift into a short movie (2021) as the strategy to save the original work and commodify the song. The theories implemented in the study include the theory of adaptation by Hutcheon and social media discourse focusing on social media commodification by Sandoval. This study is qualitative research using multiple sources of data namely text, audiovisual and digital materials. To analyze the data, this study underwent some procedures namely to observe both version of the lyrics and find the transformation, then observe and examine the transformation in the short movie adaptation. Lastly, all data is analyzed to confirm the commodification of toxic relationship by observing digital materials related to the issue, including the response on Swift’s YouTube channel. The study finds an expansion of theme in the latest version of the song by adding new lyrics that imply a toxic relationship issue. The toxic relationship issue is confirmed in the short movie adaptation by inserting narrative and cinematographic aspects. As a songwriter, producer, and director, Swift includes the toxic relationship issue in the adaptation work to commodify the trending issue. The commodification is validated by the release of the short movie adaptation on YouTube as social media that can monetize the uploaded content and gain more audiences. Keywords : commodification, film adaptation, lyric, toxic relationship, taylor swift